Oscilácia - Oszcilláció - Oscillation : Exhibition of Artists from Slovakia and Hungary. - Bartosova, Zuzana; Beke, László (Budapest : Mücsarnok Kunsthalle, 1991)
Bartusz, Juraj ; Bartuszová, Mária ; Dauciková, Anna ; Filko, Stano ; Havrilla, Vladimir ; Hrmo, Ivan ; Jankovic, Jozef ; Juhász, József R. ; Kalny, Igor ; Kern, Michal ; Knut, Martin ; Koller, Julius ; Laubert, Otis ; Melis, Juraj ; Meluzin, Peter ; Mészáros, Otto ; Pagác, Viktor Oravec - Milan ; Popovic, Vladimir ; Ronai, Peter ; Sikora, Rudolf ; Stacho, L'ubo ; Toth, Dezider ; Zelibska, Jana ; Bakos, Gábor ; Bukta, Imre ; Csorgo, Attila ; El-Hassan, Róza ; Ermezei, Zoltán ; Galantai, Gyorgy ; Gémes, Péter ; Szomlyazók, Hejettes ; Július, Gyula ; Kicsiny, Balázs ; Kiss, Péter ; Kósa, János ; Kovács, István ; Maurer, Dora ; Nemes, Csaba ; Pauer, Gyula ; Romvári, János ; Sugar, Janos ; Szabó, Agnes ; Szegedy-Maszák, Zoltán ; Szirtes, János ; Szücs, Attila ; Csoport, Ujlak ; Várnai, Gyula ; Veress, Zsolt
biografie
Oscilácia - Oszcilláció - Oscillation : Exhibition of Artists from Slovakia and Hungary, Komárno, Sixth Bastion, June 30-July 30, 1991 ; Mucsarnok, Budapest, September 19 - October 13, 1991
Engels & Hongaars & Sloveens
boek
Keywords: Hongarije; Slovenië